PROPAGAÇÃO DAS MARÉS NO GOLFÃO MARANHENSE E CENÁRIOS DE INUNDAÇÃO NA ORLA OCEÂNICA DA ILHA DO MARANHÃO - BRASIL - JANSEN, Tayssa Rauanny Silva (2024)
The propagation of the astronomical tide in the Golfão Maranhense highlights the importance of harmonic components for coastal management and navigation safety in shallow waters. The methodology includes detailed harmonic analyzes to identify the main tidal components and evaluate their influence on tidal amplitude and energy variations. The results indicate the predominance of semidiurnal tides and highlight the influence of meteorological tides on local conditions. These results are essential for optimizing port operations and coastal planning, offering crucial data to improve the understanding of tidal patterns and their applications in economic and environmental preservation activities. Furthermore, the research focuses on simulating areas susceptible to flooding caused by rising sea levels in the coastal area of Golfão Maranhense. Using advanced computer models, the study evaluates the identification of areas susceptible to flooding due to rising sea levels. Both chapters are interconnected as they deepen the understanding of coastal and tidal dynamics in the region, offering support for future management and conservation strategies in the face of the challenges posed by rising sea levels. Global climate change affects all ecosystems on Earth, including rising sea levels, which can cause flooding in coastal regions, resulting in significant environmental and financial losses. Identifying risk areas is crucial for implementing mitigation actions. The objective of this work is to identify areas susceptible to flooding resulting from rising sea levels due to climate change on Maranhão Island. This study evaluates the impact of sea level rise under two future climate change scenarios projected by AR6 (IPCC, 2021): scenarios SSP1-2.6 and SSP5-8.5, which predict a sea level rise of 0.55m and 1.02m, respectively, by the end of the 21st century. The Global Mapper software was used to apply these accumulated values to the "simulate water level rise/flooding" tool. Using this tool, it was possible to visualize and analyze potentially floodable areas under these combined scenarios. This method offers an integrated approach to assessing coastal flooding risks, considering both anthropogenic climate change and natural phenomena of water level variation, allowing a better understanding of the vulnerabilities and adaptation needs of coastal regions.